2019
DOI: 10.1186/s12981-019-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk, risk perception and uptake of HIV testing and counseling among youth men who have sex with men attending a gay sauna

Abstract: Background Men who have sex with men (MSM) are amongst populations at-risk for HIV acquisition in Thailand. In youth MSM (aged 15–24 years), the incidence of HIV infection has substantially increased. However, data on HIV risk, risk perception and HIV testing and counseling (HTC) uptake among youth MSM in hotspots are limited. Methods A subanalysis of a prospective study among Thai MSM attending a gay sauna was conducted. HIV risk and risk perception were assessed by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 26 publications
(26 reference statements)
2
33
0
4
Order By: Relevance
“…This finding is of great concern and might help explain the recent rise in HIV incidence among MSM aged 16-24 years in Brazil [7]. A recent Thai study reported similar results among MSM attending a gay sauna, where young MSM were at higher-risk compared to older MSM due to their higher risk behaviors and false perception of low HIV risk [43]. One explanation of this finding might be that younger individuals may be more fearless of HIV and/or optimistic of HIV treatment and prevention strategies [44][45][46].…”
Section: Discussionmentioning
confidence: 89%
“…This finding is of great concern and might help explain the recent rise in HIV incidence among MSM aged 16-24 years in Brazil [7]. A recent Thai study reported similar results among MSM attending a gay sauna, where young MSM were at higher-risk compared to older MSM due to their higher risk behaviors and false perception of low HIV risk [43]. One explanation of this finding might be that younger individuals may be more fearless of HIV and/or optimistic of HIV treatment and prevention strategies [44][45][46].…”
Section: Discussionmentioning
confidence: 89%
“…This could also indicate a gap in the framing of health messages which might be inadvertently excluding non-gay MSM 37 (9). A recent Thai study reported similar results among MSM attending a gay sauna, where young MSM were at higher-risk compared to older MSM due to their higher risk behaviors and false perception of low HIV risk (43). One explanation of this finding might be that younger individuals may be more fearless of HIV and/or optimistic of HIV treatment and prevention strategies (44)(45)(46).…”
Section: Discussionmentioning
confidence: 69%
“…MSM tended to have a higher number of sexual partners than heterosexual men and women [4,10,11]. In Thailand, young MSM who attended a gay sauna reported 2 different sexual partners for the last 1 month on average [12]. MSM who had multiple sexual partners were 2 times more likely to get infected from HIV, as reported by a Chinese study [13].…”
Section: Introductionmentioning
confidence: 98%